PENGARUH VARIASI WAKTU CENTRIFUGASI TERHADAP HASIL PEMERIKSAAN HEMATOKRIT METODE MAKRO PADA MAHASISWA PROGRAM STUDI D-III ANALIS KESEHATAN - Rahmat Saleh; Asnurbaety Dwiyana; , Parno , Parno (Jurnal Media Laboran, 2019)
Hematocrit examination of the wintrobe method, where erythrocyte solids are obtained by a blood centrifugation process which is determined by the speed and time centrifugation factors. As the number of examinations increases, sometimes the accuracy of centrifugation is often ignored. The purpose of this study was to determine the effect of centrifugation time variations on the results of the Macro Method hematocrit examination in D3 Health Analyst Study Program students. The method used in this study was a quasi-experimental method to find out the effect of variations in playback time on the results of the hematocrit examination of the Wintrobe method. The results of this study were obtained F-counts (0.835) and Ftables (3.35). Hematocrit centrifugation of the 25 minute macro method obtained the lowest levels of 37.5% and the highest is 68%. Centrifugation for 30 minutes obtained the lowest levels of 35.3% and the highest 66%. And lastly carried out centifugation for 35 minutes obtained the lowest levels of 37% and the highest 49.5%. Based on the above conclusions can be used for 25, 30, and 35 minutes centrifuge.